Relationship Between The Implementation of Pig Partnership Patterns With The Plasm Livestock Satisfaction Level Charoen Pokphand Ltd. In Bali - I.G.P.B.S., Dewantara; Ingriati., N.W.T.; Sriyani, N.L.P. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
Pigs are one of the livestock commodities that are potential enough to be developed. The application of a good partnership pattern will lead to satisfaction. This study aims to determine the relationship between the level of application of pig partnership patterns and the level of satisfaction of plasm farmers Charoen Pokphand ltd. in Bali. The results of the study are expected to be useful as a material consideration that is useful for core companies in making decisions and perfecting the implementation of partnerships that have taken place. The study was carried out for 3 months, at 4 regencies in Bali. The choice of the study location use the Purposive Sampling method and the determination of the sample using Quota sampling. Respondents in this study were 32 people who collaborated with Charoen Pokphand ltd. The variables observed were the application of partnership patterns and the level of satisfaction of plasm farmers. The results of the study showed that the application of the pig partnership pattern was categorized as high with an average score of 78.16%. The level of satisfaction of the plasm farmers expressed satisfaction with an average score of 77.73%. The relationship between the two was categorized as very significant (P<0.01). From the results of the research, it can be suggested that the farmers as plasm were more willing to submit complaints to the company as the core, in order to create mutual benefits.   Key words: application, satisfaction, relationship, pig livestock, farmers